The dimension of innovation in SME networks ? a case study on Cloud Computing and Web 2.0 technologies in a textile manufacturing network. (14th October 2011) - Moch, Robert; Merkel, Andreas; G?nther, Lars; M?ller, Egon
Cloud Computing and Web 2.0 technologies not only led to simplification of a variety of World Wide Web services but also contribute to a vast diversity of complex internet applications. The purpose of this paper is to find out: ?How can an SME act and get information in an innovative environment of networked partners by using web technologies?? This paper presents a case study designed with a combination of the research methods: expert interviews, data analyses and trans-disciplinary workshops including group discussion. The findings of this research base a theoretical description of the dimension of innovation of the investigated SME network. Different levels of innovation with diverse drivers and types of innovation are explored. Requirements, possibilities and obstacles for Cloud Computing and Web 2.0 technology implementations for this network are uncovered. These qualitative findings result in the development of concepts for innovative web applications regarding cooperation improvement and knowledge diffusion.